Access to Intra-Arterial Therapies for Acute Ischemic Stroke: An Analysis of the US Population - Suzuki, Shuichi; Saver, Jeffrey L.; Scott, Phillip; Jahan, Reza; Duckwiler, Gary; Starkman, Sidney; Su, Yafang; Kidwell, Chelsea S. (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Intra-arterial therapies for ischemic stroke offer promise as a means to extend the time window for acute treatment. The purpose of this study was to identify the percentage of the US population with potential access to interventional neuroradiologic expertise within 6 hours of the onset of stroke symptoms.METHODS: Hospital locations of interventional neuroradiologists were identified from the 2002 roster of the American Society of Interventional and Therapeutic Neuroradiology. Data for populations in surrounding regions were extracted from US Census 2001 data by zip code. Standard transport speeds for emergency medical services were used in our estimates of the population living within a 5-hour transport time, which was a 6-hour treatment window less a 1-hour door-to-needle time, resulting in a 200-mile radius. A 2-hour transport time, or 3-hour treatment window, reflected a 65-mile radius.RESULTS: A total of 385 interventional neuroradiologists were identified, practicing in 45 states. With a 200-mile radius, 99% of the total US population had access to neurointerventional treatment within 6 hours of symptom onset. With a 65-mile radius, 82% of the population had access within 3 hours of symptom onset. Alaska and the Mid-Northwest region covering Idaho, Wyoming, North Dakota, and South Dakota had limited coverage.CONCLUSION: Most of the US population has access to interventional neuroradiologic expertise for acute stroke therapy. These data suggest that interventional therapies that extend the time window for treating acute ischemic stroke could have a major effect on public health and merit further research development and investment.